2014
DOI: 10.5658/wood.2014.42.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Cellulose Nanofibril/Polyvinyl Alcohol Composite Nanofibers by Electrospinning

Abstract: This work undertook to prepare nanofibers of cellulose nanofibrils (CNF)/polyvinyl alcohol (PVA) composite by electrospinning, and characterize the electrospun composite nanofibers. Different contents of CNFs isolated from hardwood bleached kraft pulp (HW-BKP) by 2,2,6,6-tetramethylpiperidine-1-oxy radical (TEMPO)-mediated oxidation were suspended in aqueous polyvinyl alcohol (PVA) solution, and then electrospun into CNF/PVA composite nanofibers. The morphology and dimension of CNFs were characterized by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Instead of cellulose nanocrystal that was obtained from harsh acid hydrolysis which remained only the crystal part region, cellulose nanofibrils are a combination of amorphous and crystalline region of cellulose fibrils [15]. Figure 3 shows that cellulose nanofibrils have long entagled fibrils up to micron in length while the diameter was below than 10 nm [16]. Unfortunately, we did not have the picture of modified amidated cellulose nanofibril.…”
Section: Morphology Of Tempo-cnfmentioning
confidence: 95%
“…Instead of cellulose nanocrystal that was obtained from harsh acid hydrolysis which remained only the crystal part region, cellulose nanofibrils are a combination of amorphous and crystalline region of cellulose fibrils [15]. Figure 3 shows that cellulose nanofibrils have long entagled fibrils up to micron in length while the diameter was below than 10 nm [16]. Unfortunately, we did not have the picture of modified amidated cellulose nanofibril.…”
Section: Morphology Of Tempo-cnfmentioning
confidence: 95%
“…Chemical modification cellulose has been an important route production of multifunctional materials. biodegradable composite films for membrane and packaging applications are developed by method using modified cellulose with alcohol) in different compositions [8,15,16]. These films are characterized for mechanical, moisture absorption, gas barrier, and biodegradable properties [16,17].…”
Section: Nano Cellulose Century Fiber Compositesmentioning
confidence: 99%
“…Chemical modification of important route for the multifunctional materials. High strength membrane and by film casting with poly(vinyl erent compositions [8,15,16]. These mechanical, moisture barrier, and biodegradable properties good transparency, biodegradable ve exhibited better barrier properties with increase in percentage of modified Literature review revealed that reported cellulose nano extracted from abundantly available as widelyused in the The century nano used to cast various structural , electronic and packaging…”
Section: IIImentioning
confidence: 99%
See 1 more Smart Citation
“…The suspension was termed cellulose microfibrils (CMFs). The diameters of the CMFs are estimated to be in the range of nano to micron size (7.07 AE 0.99 nm to 10 mm) [19]. The sonication technique is an emerging method for preparing cellulose fibrils with nano size [20].…”
mentioning
confidence: 99%